Characterization Of Nano-Structured Oil Palm Ash And Its Influence As Filler In Epoxy Composites - Hashim, Mohammad Fizree (2012)
The utilization of oil palm ash, a bio-agricultural waste from oil palm mills was studied by developing it into nano-structured material and as nanofiller/reinforcement on epoxy composites. The raw oil palm ash was subjected to high-energy ball milling for 30 h and was converted into a nano-structured material. The nano-structured oil palm ash was characterized for its particle size and crystallinity index by using Transmission Electron Microscopy (TEM) and X-ray Diffraction (XRD) analysis. The crystallite size obtained from TEM and XRD was found to be 50 nm and 54.32 nm respectively, and the crystallinity index of oil palm ash was 66.54%.